REKONSEPTUALISASI PEMILIHAN KEPALA DESA SECARA LANGSUNG DIKAITKAN DENGAN KEDUDUKAN DESA SEBAGAI OTONOMI ASLI - nur ainun (Jurnal Ilmu Hukum, 2021)
Based on Article 18B paragraph (2) of the 1945 Constitution, it states that the state recognizes and respects indigenous peoples and their traditional rights as long as they are still alive and in accordance with community development and the principles of the Unitary State of the Republic of Indonesia, which are regulated in the Law. -Invit. Talking about the village cannot be separated from the original autonomy of the village and based on historical values, in which the village was formed based on the initiative of the local community with due regard to the rights of recognition or the origin of the village and the rights of subsidiarity. This study aims to determine the reconceptualization of village head elections that are directly related to the position of the village as genuine autonomy, which according to the authors that the concept of direct village head elections as regulated in Law Number 16 of 2014 concerning Villages is not properly related to the position of the village as autonomy. original. Therefore, a new concept or ideal concept is needed in the village head election system in Indonesia that takes into account the values that live in the local community and does not run away from the characteristics of the village as genuine autonomy. This research is a type of normative research, which is research conducted by examining library materials. The approach method used in this research is qualitative juridical data analysis, which is a description of the legal materials collected and because the data is not in the form of numbers that will be arranged logically and systematically and without using statistical formulas. . Furthermore, the researcher explains clearly and in detail through analysis based on applicable legal principles associated with the research topic. Keyword : Reconceptualization, Election, Village, Head, Direct, Autonomos, Original